PERAN CITRA TOKO DALAM MEMEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP NIAT BELI ULANG KONSUMEN - Santikayasa, I Made Ari; Santika, I Wayan (E-Jurnal Manajemen; Vol 8 No 2 (2019), 2019)
This study aims to explain the effect of service quality on store image, the influence of service quality on repurchase intention, the influence of store image on repurchase intention, and the role of store image mediate the influence of service quality on repurchase intention in Carrefour Bali Province. Repurchase intention is one of the company's goals because the repurchae intention is the action of the consumer to be faithful to the company. This research was conducted in the area of ??Bali Province using 100 respondents. Data collection method used is purposive sampling method with path analysis technique. The results showed that service quality had positive and significant effect to store image. Quality of service has a positive and significant impact on the repurchase intention. The store image has a positive and significant impact on the repurchase intention. Store image as a variable of mediation have an indirectly significant influence to repurchase intention through service quality variable.